What is the relationship between anorexia nervosa and miscarriage?. Issue 12 (December 2017) - O'Dowd, Stacy; Chang, Daniel
Abstract : EVIDENCE‐BASED ANSWER : Although miscarriage may be associated with binge eating disorder and atypical bulimia nervosa, no association is apparent between anorexia nervosa and miscarriage (SOR: B, retrospective case‐control study and cohort study).